Violence against Indonesian Migrant Workers - A Causal Analysis - Ardli Johan Kusuma; Michael Ryan York; Rizki Hari Wibowo (Jurnal Hubungan Internasional, 2015)
Violence and abuse against Indonesian unskilled labourers and migrant workers has become prolific and is a serious breach of human rights. This research will provide a basis to understanding physical violence and abuse against Indonesian migrant workers overseas from a policy and government perspective. This issue will be analyzed with four different perspectives including; non-government organizations working in the field, governments and legislation which are obliged to protect migrant workers against abuse, agents who send Indonesian migrant workers overseas and victims who have returned following employment overseas. Both quantitative and qualitative research methods will be applied through the compilation and analysis of statistics by government and non-government organizations, assessing trends, demographics and social factors that increase the risk of exploitation and also providing an overview of relevant legislation. Victims, witnesses, agents and other concerned parties will give testimony to provide primary data and greater insight into the issue. Understanding the causes and trends behind these phenomena will provide a sturdy foundation on which to build long term policy solutions and cooperation among nations.